Clinical features and management of carboplatin-related hypersensitivity reactions in pediatric low-grade glioma - (:unkn) unknown (SPRINGER, 2012)
The effectiveness of carboplatin and vincristine chemotherapy in the treatment of low-grade glioma (LGG) is well established. However, carboplatin hypersensitivity reactions (CHR) are a major problem leading to premature cessation of therapy. We aimed to investigate the clinical features and the management strategies in CHR, retrospectively. Fifty LGG patients treated between October 1997 and January 2008 with carboplatin and vincristine were included in the study. Clinical features, management strategies, influence of demographic factors on CHR, and success rate in terms of continuation with carboplatin therapy were evaluated. CHR were observed in 20 (40%) patients and grade I reactions were the most common. The median number of carboplatin doses administered at the first episode of CHR was nine (range 1-41). Only younger age was found to be correlated with the presence of CHR. Nine patients had carboplatin desensitization protocol; eight patients were given various combinations of premedication while three had no modification. Treatment was terminated in five patients due to CHR. Overall success rate was 75%. This is the largest single-center study conducted to investigate the frequency and the management strategies in patients with CHR who were treated with the same chemotherapy protocol for LGG. Premedication and desensitization were the preferred modifications in case of CHR. Overall, the success rate for carboplatin continuation is high in comparison to previous studies. Carboplatin can be continued successfully in many cases with CHR if reactions are managed in a timely fashion.
Keywords: Carboplatin; Hypersensitivity; Low-grade glioma; Management; PHASE-II; YOUNG-CHILDREN; CHEMOTHERAPY; DESENSITIZATION; EXPERIENCE; TUMORS; RADIOTHERAPY; EVENTS; SAFETY; COMMON